2020
DOI: 10.1101/2020.07.21.213694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delta/Theta band EEG activity shapes the rhythmic perceptual sampling of auditory scenes

Abstract: Many studies speak in favor of a rhythmic mode of listening, by which the encoding of acoustic information is structured by rhythmic neural processes at the time scale of about 1 to 4 Hz. Indeed, psychophysical data suggest that humans sample acoustic information in extended soundscapes not uniformly, but weigh the evidence at different moments for their perceptual decision at the time scale of about 2 Hz. We here test the critical prediction that such rhythmic perceptual sampling is directly related to the st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…Fluctuations of distractibility at 3 -5 Hz in the current study unveil the dynamic nature of attention, which was underappreciated in the static spotlight metaphor of attention (Posner et al, 1980). The attentional sampling of to-be-attended external stimuli (Fiebelkorn et al, 2013;Ho et al, 2017;Kubetschek & Kayser, 2021) or internal memory representation (Cruzat et al, 2021;Schmid et al, 2022;ter Wal et al, 2021) has been shown to exhibit temporal fluctuations at similar frequencies. The waxing and waning of attentional sampling may index inter-areal coordination between the attentional network and the sensory areas of the brain (Dugué & VanRullen, 2017), which is associated with the alternation between stronger and weaker attentional sampling over time (Fiebelkorn & Kastner, 2019).…”
Section: The Proneness To Distraction Is Inherently Dynamicsupporting
confidence: 52%
See 2 more Smart Citations
“…Fluctuations of distractibility at 3 -5 Hz in the current study unveil the dynamic nature of attention, which was underappreciated in the static spotlight metaphor of attention (Posner et al, 1980). The attentional sampling of to-be-attended external stimuli (Fiebelkorn et al, 2013;Ho et al, 2017;Kubetschek & Kayser, 2021) or internal memory representation (Cruzat et al, 2021;Schmid et al, 2022;ter Wal et al, 2021) has been shown to exhibit temporal fluctuations at similar frequencies. The waxing and waning of attentional sampling may index inter-areal coordination between the attentional network and the sensory areas of the brain (Dugué & VanRullen, 2017), which is associated with the alternation between stronger and weaker attentional sampling over time (Fiebelkorn & Kastner, 2019).…”
Section: The Proneness To Distraction Is Inherently Dynamicsupporting
confidence: 52%
“…With distractor-evoked behavioural and neural measures, we were able to encapsulate the temporal trajectory of distraction, which fluctuates on a subsecond temporal scale consistent with the rate of rhythmic sampling in attention (Fiebelkorn et al, 2013;Ho et al, 2017;Kubetschek & Kayser, 2021;Landau & Fries, 2012) and working memory (Cruzat et al, 2021;Schmid et al, 2022;ter Wal et al, 2021). With analysis of pre-distractor neural oscillatory phase, we were able to trace this distractibility back to a slow neural oscillatory fluctuation in inferior frontal and insular cortex (see below for an in-depth discussion).…”
Section: The Proneness To Distraction Is Inherently Dynamicmentioning
confidence: 89%
See 1 more Smart Citation